THE EFFECT OF DISASTER SOCIALIZATION ON STUDENTS KNOWLEDGE LEVEL IN DEALING WITH LANDSLIDES AT SMK NEGERI JENAWI - Laila Fitri Mayrosidah, Laila Fitri Mayrosidah; Hafida, Siti Hadiyati Nur (Universitas Negeri Surabaya, 2023)
Disaster education through socialization activities at SMK Negeri Jenawi can increase disaster knowledge that is sufficient to deal with landslides. This study aims to determine the level students knowledge of landslides and analyze the influence of socialization activities on students knowledge of landslides in facing landslides. The method used in this research is quantitative with correlation research design. The results of this study showed that 1) students perceptions of disaster socialization activities were in the strongly agree category. 2) students knowledge in landslide disaster and how to deal with it has a very good category with the percentage of correct answers above 80%. 3) the correlation of disaster socialization activities to level of knowledge of students at SMK Negeri Jenawi has a value of 0,881 and a significance value of 0.002 is smaller than significance level of 5% (0.002 < 0.05). Socialization and follow-up activities related to disaster in students at school. Keywords : Socialization, Knowledge, and Disasters